If we have a transitive relation of expressions combined with
(a < b) and (b < c) and (c < d), can this be shortened?
Yes, this can be done by
chaining the expressions with a transitive relation. Because of the order of operations, each
and operator has the same precedence which means that they will just evaluate from left to right as they appear in the entire expression.
a = 1 b = 2 c = 3 d = 4 # Original expression (a < b) and (b < c) and (c < d) # True # Using chaining, we can shorten this. # This will evaluate to the same result as above a < b < c < d # True